Deselection processes in selected academic libraries in Metro Manila - Dela Cruz, Leonida A. (1993)
This study explores the present state of deselection process or weeding in selected academic libraries in Metro Manila. It seeks to find out the nature and extent of weeding, the existence of deselection policies, if any, the deselection methods and criteria used, the methods of disposing the discarded stock and the problems encountered by the academic librarians in implementing the weeding process.